Byzantine Influence on the Serbian Customary Law in the 9th Century - Đekić, Đorđe N. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
By the 10th century Serbian law recognised the following ways of dispute resolution: revenge and appeasement, and it may be indirectly proved that there was a system of compensation. As punishments, there was banishment into exile, blinding and a death sentence. Since revenge, appeasement and compensation system appear in the pre-state period, while the death penalty has its roots in the blood feud, that indicates they are all of local origin. A question remains about the origin of banishment and blinding a fallen ruler, that is, a rival to the throne. In the first half of the 9th century the Byzantine Empire managed to reinstate its power over the Adriatic Sea, to impose itself over the Serbian states, to Christianise them and to legalise ruling families in the Serbian lands. Suffice to say that in 869 the Serbian states fight wars on the Byzantine side. Origin of influences on the ways of the punishment we seek in Byzantium, or better still, in its legal practice. It has been found that Byzantium used to send their conquered rivals to the throne into exile, punishing them by blinding them, so we draw a conclusion that in the matter of punishment, i.e. in the customary law, it exercised its influence on Serbia.